2017
DOI: 10.9775/kauiibfd.2017.023
|View full text |Cite
|
Sign up to set email alerts
|

Z Jenerasyonu Ve Kss: Üni̇versi̇te Öğrenci̇leri̇ni̇n Satin Alma Eği̇li̇mi̇ni̇n Öncülleri̇

Abstract: Objective of this research is to examine hierarchy between three factors that affect purchasing intention of Generation Z for products of companies implementing CSR projects. Since Generation Z will become target market of many companies in the shortrun, studies regarding their purchasing intention, sign of actual purchase, are valuable. Three independent factors include "Perception of Primary Motives", "General Attitudes", and "Preconditions to Prefer". Data was collected through a survey with scales measurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…In addition, the present study findings contribute that the WDBs of Generation Z and Millennials vary in response to CEI by providing empirical evidence that Generation Z reacts stronger than Millennials. The literature of generational cohort theory supports through empirical evidence that Generation Z is more conscious of CSR performance as they exhibited preferential behaviors to work and buy from the organization with higher CSR commitments (Ariker and Toksoy, 2017;Supanti and Butcher, 2019). This study findings contribute that Generation Z is ahead of older generations not only in exhibiting fondness for CSR but also disapproving CEI.…”
Section: Theoretical Contributionsupporting
confidence: 67%
“…In addition, the present study findings contribute that the WDBs of Generation Z and Millennials vary in response to CEI by providing empirical evidence that Generation Z reacts stronger than Millennials. The literature of generational cohort theory supports through empirical evidence that Generation Z is more conscious of CSR performance as they exhibited preferential behaviors to work and buy from the organization with higher CSR commitments (Ariker and Toksoy, 2017;Supanti and Butcher, 2019). This study findings contribute that Generation Z is ahead of older generations not only in exhibiting fondness for CSR but also disapproving CEI.…”
Section: Theoretical Contributionsupporting
confidence: 67%
“…Based on the mentioned above, it is obvious that different target groups may have different attitudes and behavior, including environmental awareness. The majority of previous research focused on generational stratification suggests that members of a consumer generation have mostly the same environmental behavior, and this fact influences their relationship with socially responsible brands [37][38][39][40][41][42][43][44][45][46][47]68,69]. Therefore, it is necessary to focus the communication on consumer generations with positive environmental awareness that represents the target groups of socially responsible brands.…”
Section: Discussionmentioning
confidence: 99%
“…There are many scientific papers and surveys aimed at the issue of the perception of green marketing as apart of socially responsible brands' communication from the aspect of generational stratification [37][38][39][40][41][42][43][44][45][46][47]. However, based on the dissonances of Slovak consumers recognized by Kliestikova and Janoskova, it is not possible to copy the pattern from foreign effective practice of brand value building and managing [48].…”
mentioning
confidence: 99%
“…Sharon Uche [49] examined the attitudes and perceptions of Generation Z regarding a brand or a brand's CSR and found that Generation Z consumers have more trusting relationships with brands who communicate their CSR involvement. Additionally, the research of Arıker and Toksoy [50] showed that the attitudes of Generation Z toward the implementation of CSR activities by companies are positive. Generation Z consumers have no strong intention to purchase CSR related products.…”
Section: Two Generational Cohorts and Their Perceptions Of Csrmentioning
confidence: 99%